2018
DOI: 10.1016/j.rcp.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Cognición social en esquizofrenia: aspectos cognitivos y neurobiológicos

Abstract: Social cognition in schizophrenia is currently one of the major fields of interest in studies of this disorder. It is commonly conceptualised as a set of mental operations underlying social interactions, and therefore related to the ability to interpret and predict the behaviour of others in different social contexts. The research community has defined the functional areas that constitute the domain of social cognition, including, at least, the theory of mind, sensory perception, social perception, and attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
8
0
7
Order By: Relevance
“…Several studies have shown that patients with schizophrenia experience difficulty with facial emotion recognition (Pérez-Rincón, Cortés, & Díaz-Martínez, 1999), as do their first-degree relatives (Chan, Li, Cheung, & Gong, 2010;Saracco-Alvarez, Fresán, & Escamilla-Orozco, 2013), which points to the possibility of a shared genetic load (Mendoza et al, 2011). It has even been thought that facial emotion recognition may be the key to understanding social dysfunction in schizophrenia (García, Aliste, & Soto, 2018) and therefore be a predictive variable of functional prognosis (On, Cotton, Farhall, Killackey, & Allot, 2016). There is also evidence that patients with schizophrenia are slower than controls in tasks involving facial emotion recognition (Watanuki et al, 2016) and that they recognize positive emotions such as joy better and more frequently, and have difficulty recognizing negative facial emotions such as anger, fear, sadness, and disgust (Jetha, Zheng, Goldberg, Segalowitz, & Schmidt, 2013;Romero-Ferreiro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that patients with schizophrenia experience difficulty with facial emotion recognition (Pérez-Rincón, Cortés, & Díaz-Martínez, 1999), as do their first-degree relatives (Chan, Li, Cheung, & Gong, 2010;Saracco-Alvarez, Fresán, & Escamilla-Orozco, 2013), which points to the possibility of a shared genetic load (Mendoza et al, 2011). It has even been thought that facial emotion recognition may be the key to understanding social dysfunction in schizophrenia (García, Aliste, & Soto, 2018) and therefore be a predictive variable of functional prognosis (On, Cotton, Farhall, Killackey, & Allot, 2016). There is also evidence that patients with schizophrenia are slower than controls in tasks involving facial emotion recognition (Watanuki et al, 2016) and that they recognize positive emotions such as joy better and more frequently, and have difficulty recognizing negative facial emotions such as anger, fear, sadness, and disgust (Jetha, Zheng, Goldberg, Segalowitz, & Schmidt, 2013;Romero-Ferreiro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The study of social cognition (SC) has drawn the attention of researchers, emerging as a key domain for the understanding and treatment of mental health problems [1,2]. SC can be understood independently from neurocognition (i.e., attention, language, and executive functions) and can be considered a mediator between neurocognition and social behaviour [3]. SC involves a set of mental operations underlying social interactions [4] and the capacity to understand oneself, others, social situations and interactions in a social world [5].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has supported the notion that poorer SC performance is linked to psychopathology, although most studies have primarily addressed only schizophrenia (SZ) [3,7,8]. Impairments in SC have been widely reported in individuals with SZ and have manifested as difficulties in identifying emotions, feeling connected to others, inferring people’s thoughts and reacting emotionally to others; these impairments are strong determinants of the degree of impaired daily functioning facing individuals with SZ [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations